Dream To Be The Best Dancer In Robert Adetuyi's You Got Served Beat The World Movie (2011): An Individual Psychological Approach - Pakupi, Wahyu Isnaini (2012)
The major problem of this study is: how is the major character's dream to be the best Dancer? The objectives of the study are: To analyze the film based on its structural elements and technical elements and To analyze the film especially the character of Yuson. In conducting this study, the researcher uses qualitative research which the data are based on primary data source, the movie Robert Adetuyi's You Got Served Beat the World itself. The secondary data are other data which deal with the research. In analysing the data, she applies two analysis, firtsly, structural approach which is used to analyze the elements of the movie. It consists of two elements of movie; they are narrative elements and technical elements. Secondly, the individual psychological approach is used to analyze the movie and the characteristics of Yuson. In conclusion, the writer finds that the narrative elements of movie consist of characters and characterization, setting plot, point of view and theme. The technical elements consist of mise-en-scene, cinematography, sound and editing. In individual psychological analysis, the writer concludes that Dream is something that has to be struggled. The motivation which comes from themselves can help people to make dreams come true. As a man, it is not easy to make his dreams come true. They must challenge the obstacles in their life. Dream is something that human wish in their future.